2013
DOI: 10.1016/j.geb.2013.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fast convergence in evolutionary equilibrium selection

Abstract: Stochastic best response models provide sharp predictions about equilibrium selection when the noise level is arbitrarily small. The difficulty is that, when the noise is extremely small, it can take an extremely long time for a large population to reach the stochastically stable equilibrium. An important exception arises when players interact locally in small close-knit groups; in this case convergence can be rapid for small noise and an arbitrarily large population. We show that a similar result holds when t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 27 publications
2
71
0
Order By: Relevance
“…It is assumed, however, that everyone knows the potential payoffs from alternative strategies. 12 10 This is the standard approach in the literature; see, among others, Hart and Mansour (2010), Shah and Shin (2010), Kreindler and Young (2013), Babichenko (2014), Marden and Shamma (2014).…”
Section: Nash Population Gamesmentioning
confidence: 99%
“…It is assumed, however, that everyone knows the potential payoffs from alternative strategies. 12 10 This is the standard approach in the literature; see, among others, Hart and Mansour (2010), Shah and Shin (2010), Kreindler and Young (2013), Babichenko (2014), Marden and Shamma (2014).…”
Section: Nash Population Gamesmentioning
confidence: 99%
“…The case where players revise their decisions following noisy best-response dynamics was considered in [3]- [7], i.e., players prefer their best response, but do not always follow it. Reference [3] showed that noisy best-response dynamics with global interaction result in every player choosing the risk-dominant strategy.…”
Section: Related Workmentioning
confidence: 99%
“…Reference [6] characterized the expected waiting time until all players choose the risk-dominant strategy under noisy best-response dynamics on random graphs. When the degree of risk-dominance exceeds a threshold, the riskdominant strategy spreads under noisy best-response dynamics and gobal interaction, and the expected time for this to happen is bounded independently of the system size [7].…”
Section: Related Workmentioning
confidence: 99%
“…[7] Interesting simulation results have been conducted for heterogeneous populations in [11], [12] and [13] where the agents are associated with different payoff matrices. Some mathematical statements have been provided in [14] and [15] The work was supported in part by the European Research Council (ERCStG-307207).…”
Section: Introductionmentioning
confidence: 99%
“…Ramazi and M. Cao are with ENTEG, Faculty of Mathematics and Natural Sciences, University of Groningen, The Netherlands, {p.ramazi, m.cao}@rug.nl for the myopic best response update rule [15] but only for the case when the population is homogeneous and the game is symmetric. Some researchers have studied the stochastic stability of different strategies in the population when the update rule is noisy [16] [14]. Besides the results addressing the stability issue of strategically interacting populations, there is an emerging trend to investigate how to control such populations.…”
Section: Introductionmentioning
confidence: 99%